(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2009)
We propose some short considerations about the lacklustre condition of latin epigraphy nowadays; in the meantime we illustrate the latest novelties (discoveries, researches, projects and activities) in the field of Latin Epigraphy in Milan and in its neighbourhood.